Infant and Child Mortality in Andhra Pradesh Analysing changes over time and between states - Edoardo Masset and Howard White
Most countries of the world are reducing infant and child mortality too slowly to meet the Millennium Development Goal of a two-thirds reduction by 2015. Yet, some countries and regions have achieved impressive reductions, Kerala in India being one example. This paper examines the determinants of infant and child mortality in Andhra Pradesh, where the Young Lives project is taking place, and Kerala and the factors explaining their differential performance. The determinants of mortality are estimated using a Cox proportional hazards model. Infant mortality is found to depend on biological factors, including mother's age and birth order, and also factors related to health service provision such as tetanus injection and use of antenatal services. Economic well being is not significant once these other factors are taken into account. By contrast, economic well-being is a significant determinant of child mortality, but substantially outweighed in importance by other factors such as maternal education and knowledge of health practices (ORS) and access to safe water. The data also show gender discrimination in Andhra Pradesh, notably toward girls with only female siblings, which is absent from Kerala. We conclude that raising service levels across India toward the levels found in Kerala is a necessary step toward meeting the MDGs, and that the success of these efforts is reinforced by female empowerment.